Covid 19 Inovasi sebagai Nilai Jual Produk "Kita Local Pride" (Studi Kasus Brand Tas Lokal di Banyuwangi) - Imanda Anggraita Sakina (INTERDISCIPLINARY JOURNAL ON LAW, SOCIAL SCIENCES AND HUMANITIES, 2020)
Globalization presents a challenge to economic activities, especially those doing small and middle-class businesses in Indonesia. The real challenge is that foreign products are more easily introduced into Indonesia's consumer markets that can boost the sales competition of products produced by local producers. The research aims to find out how the phenomenon of foreign products is faced by local businesses by utilizing technological development and conducting market segmentary-level analysis. The research was done by collecting data from the founder's source "Kita Local Pride" local bag brand in Banyuwangi, East Java, by Ahmad Irgi Fahrezy through interviews with a list of structured questions and types of open questions. The result is that "Kita Local Pride" appears to be based on sources' concerns about the existence of local products in the predominantly foreign consumer markets. The innovation is pinning a brand that has an inclusive philosophy of society, especially young people, as a strategy to attract potential consumers. Innovation is also made in bag design that is dominated by a variety of colors that match young people well. Innovation is also made by marketing products using social media.